Advertising results in economic growth - A new methodological perspective - Eremin, Artem; Nagy, Ákos (Marketing & Menedzsment, 2019)
The present research will introduce a new methodology of analyzing advertising’s impact on GDP. By juxtaposing the discrepancies in the GDP measurement with the advertising expenditures in the US, the paper will show that there is a significant relationship between GDP’s growth and adspend. Granger test of causality will establish the causality running from advertising to GDP. Based on that, it will be argued that advertising should be treated as an investment in both accounting and calculation of GDP by expenditure method.